Not so simple: The multidimensional nature and diverse origins of political ideology. Issue 3 (27th June 2014) - Feldman, Stanley; Huddy, Leonie
Abstract: At odds with Hibbing et al., we argue that political ideology is best explained by at least two dimensions linked to economic and social ideology. In addition, Hibbing et al's claim that conservatism is grounded in a heightened sensitivity to negative outcomes, something closely tied to the personality trait of neuroticism, does not fit with the established personality correlates of political ideology. Conscientiousness and a lack of openness to experience are linked to conservatism but there is no established connection to neuroticism.